Adapting Human Factor toward Well-Being and Performance: A Case Study of Ergonomics on Hybrid Work Environment - Samuel PD Anantadjaya; Timotius Agus Rachmat; Irma M Nawangwulan; DC Ethan Samuel; Pramudhio RA Widyatmoko; Waraney Dendeng; Daniella CE Samuel (CV. Media Digital Publikasi Indonesia, 2026)
This qualitative literature-based study explores the application of ergonomics, also known as human factors engineering, in contemporary hybrid work environments to optimize employee well-being and performance. Drawing on a systematic thematic analysis of 52 peer-reviewed publications (2024–2025) using NVivo software, the research consolidates knowledge across the International Ergonomics Association’s 3 core domains: physical, cognitive, and organizational ergonomics. Findings reveal that hybrid work has intensified ergonomic risks: improvised home workstations frequently lead to musculoskeletal disorders and fatigue (physical domain); constant digital connectivity and poorly designed interfaces drive technostress, cognitive overload, and burnout (cognitive domain); while inadequate organizational policies, leadership support, and communication structures exacerbate disengagement and blurred work–life boundaries (organizational domain). Crucially, the domains are highly interdependent: physical discomfort amplifies cognitive load, organizational decisions shape both physical and cognitive demands, and holistic interventions addressing all three domains yield the strongest outcomes. Supported by visual and quantitative analyses (word clouds, tree-maps, cluster maps, and dendrograms), the study confirms that ergonomics in hybrid settings must move beyond isolated physical adjustments to become a strategic, integrated system. Organizations that embed supportive policies, provide tangible ergonomic resources, and foster a proactive ergonomic culture achieve measurable gains in employee health, engagement, retention, and productivity. The paper concludes with evidence-based recommendations for employers, employees, and future research, emphasizing that holistic ergonomics is no longer optional but a core driver of sustainable performance and organizational resilience in the era of hybrid work.